The Making of International Communication Standards: Towards a Theory of Power in Standardization - ten Oever, Niels; Milan, Stefania (Journal of Standardisation, 2022)
In this critical literature review, we provide an overview of the history of international communication standards to argue that a comprehensive theory of standardization needs not only to be a theory of technology or institutional configuration(s), but also a theory of power. Such a theory should account for three forms of power respectively in the realms of economy (control over capital), politics (control over practice), and ideology (control over rationalities). By providing an overview starting the standardization of the telegraph, to the Internet, and wireless telecommunication technologies, most notably 5G, we show how these different aspects play significant roles in standardization and need to be accommodated in a non-deterministic manner. Finally, we explore whether there is a role for the public interest in such a theory of power in standardization.